PLURALITAS BUDAYA BERAGAMA MAHASISWA; PENDEKATAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Hidayah, Ulil; Sholikhah, Khotimatus (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Pluralism is both a hope and a challenge for some groups, especially in terms of detailed differences. While religious differences have become a long topic of discussion resulting in a formulation of harmony between religious communities, what is more detailed is the differences in religious culture within Muslims. This research describes the religious cultural model of students at STAI Muhammadiyah Probolinggo based on the Muhammadiyah and NU religious groups. The object of this research is students at the Probolinggo Muhammadiyah college whose student population is dominated by representation of two large community organization groups in Indonesia, namely Muhammadiyah and Nahdlatul Ulama'. Data was obtained from direct observations and student answers in the mid-semester exam for the multicultural PAI course regarding students' attitudes towards viewing differences in other religious cultures. The results of the analysis found that students who have different religious cultures from other groups have a tolerant attitude but still have an ethnocentric attitude. So, through the multicultural Islamic Religious Education curriculum, it is necessary to thoroughly instill the ideology of multiculturalism and pluralism in students as a form of higher education's efforts to direct students to become agents of change in a peaceful and humanist civilization.